Prognostic value of preoperative glucose to lymphocytes ratio in patients with resected gastric cancer - Yıldırım, Murat Baki; Özkan, Murat Bulut (Journal of Surgery and Medicine, 2021)
Background/Aim: There are no definitive tests that determine postoperative survival in gastric cancer. Simple and cheap laboratory markers are needed for clinicians to guide them preoperatively. The aims of our study were to analyze the importance of preoperative glucose-lymphocyte ratio (GLR) in the prognosis of patients with gastric cancer (GC), and to compare the success of GLR in predicting prognosis with the success of neutrophil-lymphocyte ratio (NLR) and C-reactive protein-albumin ratio (CAR). Methods: We carried out a cross-sectional study on 196 GC patients. CAR, NLR and GLR values were calculated from the blood samples taken 24 hours before the surgery. Lymphovascular invasion, serosal invasion, and the number of metastatic lymph nodes were determined, and the prediction ability of glucose to lymphocyte ratio (GLR), neutrophil to lymphocyte ratio (NLR), and C-reactive protein to albumin ratio (CAR) were evaluated. In addition, the effect of GLR and NLR on the ability to predict overall survival was assessed. The mean follow-up period was 37 (6-69) months. Results: A moderate and weak positive correlation was found between GLR, NLR and the number of metastatic lymph nodes (r=0.415, P<0.001; r=0.193, P=0.007, respectively). GLR and NLR were significant for predicting lymphovascular and serosal invasion (P<0.001). CAR was insufficient in lymphovascular invasion differentiation (AUC (95% CI): 0.582 (0.501-0.662)) (P=0.529) and serosal invasion differentiation (P=0.529). GLR significantly predicted overall survival (P=0.002). Patients with a GLR value of <4.12 had a significantly longer overall survival than those with GLR>4.12. NLR was insignificant for overall survival (P=0.233). Conclusion: GLR value may contribute to the planning of the therapy process by predicting both the prognosis of the disease and the overall survival before surgery.